Determination of Hydroquinone in a Square Wave Voltammetry based on Screen Printed Carbon Electrode - Alfita Safitri; Ani Mulyasuryani; Rachmat Triandi Tjahjanto (The Journal of Pure and Applied Chemistry Research, 2015)
Hydroquinone is a phenolic compound are often used extensively in the cosmetics industry as whitening agent. This compound is very toxic and their use should be monitored. Due to the impact of hydroquinone, the use of hydroquinone restricted by BPOM (Food and Drug Regulatory Department in Indonesia) maximum by 0.02%. The aim of this study was to establish a new simple sensitive voltammetry method for determination of hydroquinone using screen printed carbon electrode (spce). In this study, linear concentration range, limit of detection, sensitivity and accuracy were investigated. Before the determination of parameters analysis, the method require the optimization of method parameters such as frequency and pulse height. This study were showed that the measurement of hydroquinone with square wave voltammetry method has linear concentration range 1 - 100µM, limit of detection 23.4µM, sensitivity 0.075µM/µA and accuracy 0.9969. The proposed method was succesfully applied in whitening cream cosmetic samples with good enough results.